Optimal duration of altitude training for the National Open Water Team of Ecuador - Enderica Salgado, Juan Fernando; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of the present research was to determine the importance of the permanence of four weeks of training at altitude by the National Open Water Team of Ecuador. Several time tests were carried out in different specific distances: 100, 200 and 800 meters’ freestyle. In addition to these evaluations, lactic acid test was carried out, since it is the best indicator of physical effort, and can determine the dosage of load or intensity of work in athletes of high sports performance. For this research, 4 swimmers from the elite category were evaluated, with a training methodology where different types of training are developed to increase their capacities. The research design was exploratory-quantitative. The swimmers evaluated presented a significant improvement in the course of the weeks programmed in this study. It was concluded that the permanence of the 4 weeks of preparation at altitude contributed to the improvement of the completion times in the different distances, being the fourth week in which the swimmers improved all their records and the lactate tests.